Human–computer interaction in evolutionary visual software analytics - González-Torres, Antonio; García-Peñalvo, Francisco J.; Therón, Roberto (Computers in Human Behavior, 2013)
Software evolution is made up of changes carried out during software maintenance. Such accumulation of changes produces substantial modifications in software projects and therefore vast amounts of relevant facts that are useful for the understanding and comprehension of the software project for making additional changes. In this scenario, evolutionary visual software analytics is aimed to support software maintenance, with the active participation of users, through the understanding and comprehension of software evolution by means of visual analytics and human computer interaction. It is a complex process that takes into account the mining of evolutionary data, the subsequent analysis of the mining process results for producing evolution facts, the use of visualizations supported by interaction techniques and the active participation of users. Hence, this paper explains the evolutionary visual software analytics process, describes a framework proposal and validates such proposal through the definition and implementation of an architecture.